(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
On the basis of comparison the translation of texts of different functional styles the essence of adequate translation is specified, conditions for a holistic analysis of the original and the translation are formulated.